EFL Students’ Ability and Barriers in Report Text - Prasetyaningrum, Ari; Asrobi, Maman; Husnu, Muhammad; Royahin, Saopia (English Language in Focus (ELIF), 2022)
The research purposes were to determine the students’ ability along with the barriers in writing report texts of the eleventh graders at MA NWDI Perian. This research adopted a mix method of sequential explanatory analysis (quantitative descriptive-qualitative).  The Instruments were written tests and interviews. Students were first asked to write report texts to determine their ability and then they were asked a series of questions related to the data results. Based on the results, the mean score was 52.19 and the passing grade for English was 70. This indicates that the participants’ ability in writing report texts is poor or below standard. There are five components that are assessed, and participants' ability levels in these five components are still relatively low. The percentages of each assessment were as follows: content 21%, organization 21%, vocabulary 18%, language 18%, and mechanic 22%. According to the results of qualitative data analysis, the barriers in writing report texts were content, organization, vocabulary, language, and mechanics. In addition to those students barriers, there are other factors that should be considered in writing tasks, such as motivation, lexicogrammar features, paragraph elements, or three main factors that influence students' writing skill, namely psychological, sociocultural and linguistic.  Furthermore, this study was conducted while the pandemic was still widespread and the interaction of teachers and students during the teaching and learning process were only conducted via virtual setting. This, of course, makes teachers less effective in delivering lessons, particularly in writing, which requires extensive practice, proofreading, discussion, and revision activities. In addition, factors such as space barriers and, in some cases, network restrictions and the use of unappropriate teaching methods or strategies, all have an impact on students' writing skills.